Complications of Ventriculoperitoneal Shunt for Idiopathic Intracranial Hypertension: A Single-Institution Study of 32 Patients. Issue 2 (June 2021) - Brune, Anthony J.; Girgla, Taania; Trobe, Jonathan D.
Abstract : Background: Because there are no head-to-head studies of the efficacy of surgical options in the treatment of medically-intractable idiopathic intracranial hypertension (IIH), procedure selection is often based on expected complications. Cerebrospinal fluid (CSF) diversion by shunting has been reported to have a 23%–67% rate of shunt failure. But these figures derive from small cohorts or studies that do not separate the complication rates of the different shunt options—ventriculoperitoneal (VP), lumboperitoneal (LP), and ventriculoatrial (VA). The complication rate of LP shunts seems to be higher than that for VP shunts, the procedure currently in widest use. Our experience with VP shunts for IIH over the past decades suggests that the complication rate for that option is lower than reported series would suggest. Methods: Retrospective single-institutional study using a search engine that finds all text mentions of particular terms. We searched for the terms ("IIH" OR "Idiopathic intracranial hypertension" OR "PTC OR "pseudotumor") AND ("VP Shunt" OR "ventriculoperitoneal") over the period 1998 to 2018. From 490 "hits, " only 32 patients met entry criteria: diagnosis of IIH confirmed at our institution, including examination in a neuro-ophthalmology clinic showing papilledema, elevated opening pressure on lumbar puncture or a consistently elevated intraparenchymal pressure on Codman intracranial pressure (ICP) monitoring, neuroimaging and CSF studies consistent with a diagnosis of IIH, and at least 1 year of follow-up in our neuro-ophthalmology or neurosurgery clinics. Results: Shunt failures occurred in 6 (18.7%) of 32 patients, which included elevated ICP due to obstruction or discontinuity of the shunt, over-drainage, infection of the shunt system, or intractable abdominal pain or infection. None of these failures caused permanent worsening of vision, neurologic morbidity, or death. But they entailed considerable medical care. Placement of VP shunts also aroused patient fear of complications, precipitating 38 emergency visits in 14 patients for "false alarms." Conclusions: In this series of 32 patients, the largest retrospective study of VP shunts for IIH, there was an 18.7% failure rate, lower than previously published smaller series have disclosed. But among patients who suffered complications, a saga of intensive medical care often occurred. Placement of the shunt also aroused patient fear of complications, leading to many medical encounters required to rule out complications.